PENGARUH EKSTRAK UMBI BAWANG PUTIH DAN UMBI BAWANG MERAH TERHADAP LUKA BAKAR PADA KELINCI - Barus, Bunga Rimta; Lestari, Indah (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2018)
Burns are one of the most common types of injuries in the community. The content of alliin in garlic (Allium sativum L) and onion (Allium cepavarascalonicum) is believed to help heal burns, with its biological activity as anti-aggregation of platelet cells, boost fibrinolysis and as an anti-bacterial. Objective of this research is to know the effect of gaelic extract (Allium sativum L) and red onion (Allium cepa var ascalonicum) to burn on rabbit.The methodology of this research is an experimental method based on a complete randomized design.sample used in this research and onion bulbs taken in Berastagi Subdistrict, Karo Regency, North Sumatera Province.Result of this research show that subjects of Garlic extract with 15% concentration gave the fastest healing effect on 7th day, 10% and 5% dose gave healing effect on the 8th day. Giving onion bulbs extract at 15%, 10% and 5% concentration gave healing effect of burn on 8th day. The healing of burns in the comparison group was on the 8th day while the longest burn healing in the control group was on the 10th day. Conclusion is an effect that can be found in the extract of garlic and onion extract to the burn on the rabbit.